Analysis of pesticide residues in the fresh fruits by using gas chromatography with electron capture detector (GC-ECD) - Nur Atiqah , Aminudin (2013)
Recently, pesticides are extensively used to ensure high crop yields which is used during production and post-harvest treatment. However, the increased use of the pesticides has resulted in pollution of the environment and also has caused many associated shortterm and long-term effects on human health. Thus, in the present study, an effort has been made to analyze the pesticide residues in the fresh fruits purchased from the fruit markets in Gambang, Kuantan. Gas chromatography with selective electron capture detector (GCECD) was used to determine the amount of Chiorpyrifos pesticide residues in the apple and pear samples that is firstly being washed by distilled water and fruits detergent, respectively. From the both fruit samples, it shows that both apple and pear samples were positive with the Chlorpyrifos residues within the range of 0.02mg kg' to 0.06 mg kg1, respectively. From the results, it also shows that by using fruits detergent, it is effectively used in reducing the amount of-the pesticide residues in the fruits by range of 35% to 40%. However, from the results of the pesticide residues of both samples, the finding shows that no pesticides detected exceeded the Maximum Residue Limits (MRLs) established by World Heatlh Organization (WHO) which is 1.0 mg kg' for both fruits. Thus, it shows that despite a high occurrence of pesticide residues in the fruit samples, it could not be considered as a serious public health problem. Nevertheless, an investigation and research into continuous monitoring and more strict regulation of pesticide residues in the food commodities is recommended.